Confinement of CoP Nanoparticles in Nitrogen‐Doped Yolk‐Shell Porous Carbon Polyhedron for Ultrafast Catalytic Oxidation. (11th September 2020) - Zhu, Changqing; Zhao, Shafei; Fan, Zhongwei; Wu, Haide; Liu, Fuqiang; Chen, Zhaoxu; Li, Aimin
Abstract: Catalytic oxidation of toxic organic pollutants in water urgently requires improved efficiency for practical application. Here a wrapping‐pyrolysis strategy is exploited to convert CoP nanowires‐threaded ZIF‐8 into CoP nanoparticles‐confined nitrogen‐doped yolk‐shell porous carbon polyhedra, featuring high‐density active sites, and high adsorbability, dispersibility and conductivity (4‐High). The nanoreactor efficiently activates peroxymonosulfate for bisphenol A (BPA) degradation over a wide pH range and in saline solutions. The apparent kinetic rate constant (18.96 min −1 ) is the highest reported to date and exceeds those of reported catalysts by 1–2 orders of magnitude. Experimental and theoretical evidence reveals that the catalysis occurs at the Co4 P4 @graphitic nitrogen‐doped graphene site to produce surface‐bound SO4 − and induce direct electron abstraction for BPA degradation. The high catalytic activity is attributed to the unique yolk‐shell structure which concentrates catalytic and adsorptive sites within a confined space, as well as to the porous carbon polyhedron with high dispersibility and conductivity for fast mass and electron transport. Moreover, a fluidized‐bed catalytic unit is constructed and enables continuous zero discharge of BPA and easy nanocatalyst recycling. This work will guide "4‐High" catalyst design to improve future deep water purification technology. Abstract : Confining CoP nanoparticles into the interior cavity of a nitrogen‐doped yolk‐shell porous carbon polyhedron creates a novel "4‐High" nanoreactor featuring high‐density catalytic sites, and high adsorbability, dispersibility, and conductivity for peroxymonosulfate activation. Organic pollutants are degraded at an unprecedented rate via surface‐bound SO4 − and direct electron abstraction with Co4 P4 @graphitic nitrogen‐doped graphene as the active center.